Does Ricosre Learning have the potential to improve Students' Decision Making Ability? - Aprilyani Aprilyani; Susriyati Mahanal; Sulisetijono Sulisetijono (Jurnal Pendidikan Sains, 2020)
Abstract: The RICOSRE learning model can influence the decision making skills of class X students of two high school. The research used was quasi-experimental with pretest and posttest non-equivalent control group design. The research sample was students of two high school which are determined by random sampling. Data collected in the form of pretest and posttest scores. It used Anakova technique to analyze the data. The result confirmed that the RICOSRE learning model affected the decision making skills of class X students with an increase of 63.69%.Abstrak: Model pembelajaran RICOSRE dapat berpengaruh terhadap keterampilan pengambilan keputusan siswa kelas X di kedua SMA. Penelitian yang digunakan adalah kuasi eksperimen dengan pretest posttest non-equivalent control group design. Sampel penelitian, yaitu siswa di kedua SMA yang ditentukan secara random sampling.  Data yang dikumpulkan berupa skor pretest dan posttest. Analisis data menggunakan teknik Anakova dan hasilnya yaitu model pembelajaran RICOSRE berpengaruh terhadap keterampilan pengambilan keputusan siswa kelas X dengan peningkatan sebesar 63,69%.